Model-based Cost-effectiveness of State-level Latent Tuberculosis Interventions in California, Florida, New York, and Texas. (25th June 2020) - Jo, Youngji; Shrestha, Sourya; Gomes, Isabella; Marks, Suzanne; Hill, Andrew; Asay, Garrett; Dowdy, David
Abstract: Background: Targeted testing and treatment (TTT) for latent tuberculosis (TB) infection (LTBI) is a recommended strategy to accelerate TB reductions and further TB elimination in the United States. Evidence on cost-effectiveness of TTT for key populations can help advance this goal. Methods: We used a model of TB transmission to estimate the numbers of individuals who could be tested by interferon-γ release assay and treated for LTBI with 3 months of self-administered rifapentine and isoniazid (3HP) under various TTT scenarios. Specifically, we considered rapidly scaling up TTT among people who are non–US-born, diabetic, living with human immunodeficiency virus (HIV), homeless or incarcerated in California, Florida, New York, and Texas—states where more than half of US TB cases occur. We projected costs (from the healthcare system perspective, in 2018 dollars), 30-year reductions in TB incidence, and incremental cost-effectiveness (cost per quality-adjusted life-year [QALY] gained) for TTT in each modeled population. Results: The projected cost-effectiveness of TTT differed substantially by state and population, while the health impact (number of TB cases averted) was consistently greatest among non–US-born individuals. TTT was most cost-effective among persons with HIV (from 2828/QALY gained in Florida to 11 265/QALY gained in New York) and least cost-effective among people with diabetes (from 223 041/QALY gained in California to 817 753/QALY in New York). Conclusions: The modeled cost-effectiveness of TTT for LTBI varies across states but was consistently greatest among people with HIV; moderate among people who are non–US-born, incarcerated, or homeless; and least cost-effective among people with diabetes. Abstract : The cost-effectiveness of targeted testing and treatment for latent tuberculosis infection varies across states but was greatest among people living with HIV; moderate among people who are non–US-born, incarcerated, or homeless; and least cost-effective among people living with diabetes.